1993
DOI: 10.1111/j.1365-2265.1993.tb02403.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in patients with endogenous subclinical hyperthyroidism: Is this thyroid status a risk factor for osteoporosis?

Abstract: This study indicates that the bone mineral density of the lumbar spine, femoral neck and the midshaft of the radius are not significantly decreased in premenopausal patients with endogenous subclinical hyperthyroidism resulting from a solitary autonomously functioning thyroid nodule. Conversely, findings hint at the possibility that long-lasting endogenous subclinical hyperthyroidism may be a contributing factor to the development of osteoporosis in some post-menopausal women, mostly at sites where cortical bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1
9

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 32 publications
3
76
1
9
Order By: Relevance
“…In line with this, the skeleton also seems to be in¯uenced in patients with endogenous subclinical hyperthyroidism in a way which suggests slight thyroid hormone excess at the tissue level: postmenopausal women with endogenous subclinical hyperthyroidism due to a multinodular goitre have reduced bone mass in comparison to women with normal TSH (27). Furthermore, we have shown that treatment of such patients with radioiodine with the aim of normalising serum TSH, results in increased bone mass as compared with those not treated (28).…”
Section: Discussionsupporting
confidence: 56%
“…In line with this, the skeleton also seems to be in¯uenced in patients with endogenous subclinical hyperthyroidism in a way which suggests slight thyroid hormone excess at the tissue level: postmenopausal women with endogenous subclinical hyperthyroidism due to a multinodular goitre have reduced bone mass in comparison to women with normal TSH (27). Furthermore, we have shown that treatment of such patients with radioiodine with the aim of normalising serum TSH, results in increased bone mass as compared with those not treated (28).…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have been focused both on endogenous and drug-induced subclinical hyperthyroidism (Franklyn et al 1992, Kung et al 1993, Giannini et al 1994, Marcocci et al 1994, McDermott et al 1995, Muller et al 1995, Rosen et al 1998). In two studies, patients with nodular goitre and endogenous subclinical hyperthyroidism had lower BMD than comparable normal subjects (Mudde et al 1992, Foldes et al 1993, although in one trial significant reductions in BMD occurred only in postmenopausal and in sites rich in cortical bone (Foldes et al 1993). Some authors described decreased BMD in pre-and postmenopausal women with a significant negative correlation with T3 levels (Tauchmanova`et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Even low-normal TSH levels can already be associated with low BMD and increased risk of osteoporosis in healthy postmenopausal women (4,5,26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, thyrotropin (TSH) is a negative regulator of bone remodeling, inhibiting the formation and survival of osteoclasts and the differentiation of osteoblasts (3). Also, it has been proposed that low TSH levels, per se, can predispose to osteoporosis and fragility fractures (4,5,6). However, the studies investigating the effects of endogenous subclinical hyperthyroidism on the skeleton are scarce, with most of them reflecting the effect of supraphysiologic doses of thyroid hormone to suppress TSH secretion in the treatment of differentiated thyroid carcinoma or nontoxic goiter and providing conflicting results (7).…”
Section: Introductionmentioning
confidence: 99%